Long Non-coding RNA RP11-395G23.3 Acts as a Competing Endogenous RNA of miR-124-3p to Regulate ROR1 in Anaplastic Thyroid Carcinoma - Qin, An-Cheng; Qian, Yi; Ma, Yu-Yuan; Jiang, Yong; Qian, Wei-Feng (Frontiers in Genetics, 2021)
Anaplastic thyroid carcinoma (ATC) is one of the most aggressive human malignancies with poor prognosis. However, the underlying mechanisms of ATC remained to be elucidated. Recently, increasing studies have focused on competitive endogenous RNA (ceRNA) to discover valuable biomarkers for the diagnosis of ATC. The present study identified 705 differentially expressed mRNAs and 47 differentially expressed lncRNAs. And the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were also conducted. Additionally, the lncRNA/miRNA/mRNA ceRNA network was constructed which included 1 103 regulatory relations. The upregulation of RP11-395G23.3 in ATC cells was confirmed by qRT-PCR. In the loss of function assays, results suggested silencing of RP11-395G23.3 inhibited cell proliferation and induced cell apoptosis. Mechanically, RP11-395G23.3 could increase ROR1 via sponging miR-124-3p as a ceRNA. Moreover, ROR1 expression was decreased with the downregulation of RP11-395G23.3, but was rescued by the co-transfection of miR-124-3p inhibitor in ATC cells. Our research suggested RP11-395G23.3/miR-124-3p/ROR1 axis potentially acted as a potential target for the diagnosis of ATC.